Effect of Fermented Feed on Cattle Weight at Pondok Rawa Village, Deli Serdang Regency, North Sumatera - Hesti Wahyuningsih; Hotnida Sinaga; Liana Dwi Sri Hastuti; Fachri Fauzi; Wulan Apridamayanti; Silfy Anisa Nasution; Wira Khairulsyah; Arbi Maulana (Berkala Ilmiah Biologi, 2023)
Abstract: Cattle farming in Indonesia, especially in North Sumatra, is still a secondary livelihood for breeders. Treatment and processing of beef are generally done in the traditional way. The success of the beef cattle business is very dependent on the fulfillment of nutrients that affect livestock health. Therefore, quality and sustainable feed is an important factor in livestock cultivation technology. The purpose of this study was to determine the effect of fermented feed on cattle weight at a small cattle farm in Pondok Rawa Village, Deli Serdang Regency, Sumatera Utara. Fermented feed is formulated by mixing corn ash and palm oil cake (5:1), coarse salt, molasses, and EM4 into chlorine-free water. The feed was stored in PP plastic and incubated for 7 days. Five cows chosen randomly were given fermented feed every day for 1 month while the other 5 cows were only given forage. All test cattle were about 4 years old and weighed weekly and the data were statistically analyzed using ANOVA in JASP 0.16.4. The results showed that the average weight gain of one cattle fed with fermented feed (1.54 kg/week) was higher than forage treatment (0.69 kg/week). This result was validated and substantiated by ANOVA test result showing that value of p < 0.05.